Learning Media for Environmental Education, What Can the Scopus Database Tell Us? A Review - H. Husamah; Abdulkadir Rahardjanto; Tutut Indria Permana; Nurdiyah Lestari (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2025)
Environmental education plays a pivotal role in fostering sustainability awareness and behavioral change, especially when supported by effective pedagogical tools. In recent years, the integration of digital technologies—including mobile applications, augmented reality, videos, and interactive platforms—has increasingly reshaped traditional teaching strategies to enhance cognitive development and environmental literacy. However, persistent challenges such as limited resources, technological infrastructure, and teacher preparedness continue to hinder widespread adoption. This study contributes by mapping how digital learning media have evolved within environmental education research, highlighting conceptual shifts and emerging interdisciplinary intersections. Unlike prior reviews, this article offers a combined bibliometric and qualitative analysis of 17 Scopus-indexed articles published 2018-2023, using Scopus AI and VOSviewer tools. Results show that digital media—such as gamification and social platforms—appear to be more promising than conventional methods in promoting environmental understanding and engagement. The most prominent research themes include environmental education, sustainable development, and learning media, with increasing attention to mobile learning, augmented reality, and interdisciplinary strategies. Five key conceptual clusters emerged: (1) sustainability integration in higher education, (2) innovative pedagogies, (3) links between environmental literacy and behavior, (4) cross-disciplinary approaches (e.g., through language learning), and (5) utilization of digital media. These findings underscore the transformative potential of technology while advocating for adaptive and inclusive learning designs. Nevertheless, the results should be interpreted in light of limitations related to database scope and publication context. Future research should investigate long-term behavioral outcomes, culturally adaptive media design, applications of AI, and strategies to bridge equity gaps across diverse educational settings.